Serological and epidemiological surveillance of avian influenza and other zoonotic pathogens in Malaysian Borneo - Klim, HJ (2024)
Changing landscapes across the globe, but particularly in Southeast Asia, are pushing humans and animals much closer together and increasing the likelihood of zoonotic spillover events. Malaysian Borneo is hypothesised to be at high risk of spillover events due to proximity between reservoir species and humans caused by recent deforestation in the region. I began this DPhil thesis by quantifying the relationship between land use change and human-animal contact using an environmentally stratified cross-sectional survey conducted in Malaysian Borneo in 2015. These data were used to identify risk factors for contact and generate geostatistical models predicting animal contact under current and future climate conditions. I then studied the possibility of spillover in this region through serosurveys of influenza A virus (IAV), filoviruses, paramyxoviruses, and coronaviruses. These surveys depended on a variety of immunoassays including enzyme-linked immunosorbent assays (ELISAs), pseudotyped neutralisation, flow cytometry, and multiplexed approaches which were coupled with geospatial analyses where possible. The results of these studies highlight a variety of risk factors associated with agricultural intensification that are predictive of animal contact. Serological analysis identified evidence of possible IAV spillover, seasonal coronavirus exposure, and one unusual filovirus seropositive. This thesis also includes a phylogenetic analysis of Group 2 IAVs with pseudoneutralisation that was completed in a different research group. There are many avenues for future study based on the results and novel approaches presented here. This research will help inform public health efforts in at-risk populations and can improve pathogen surveillance efforts in Malaysian Borneo.